2021
DOI: 10.1007/s10639-021-10440-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effectiveness of a mobile writing application for supporting handwriting acquisition of students with dysgraphia

Abstract: , 171 pages Handwriting is one of the most important and essential skills for both literacy and beyond. However, some students may have difficulty in writing. Dysgraphia, expressed as the disorder of written expression, is the state of writing skills being below the expected level of intelligence, age, and education of the student. The main purpose of the study is to examine the effectiveness of the mobile writing application for students with dysgraphia and to determine whether there is an improvement in writ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…They found that mobile apps might be a reliable option for students with disabilities who cannot afford assistive technologies. Hopcan and Tokel (2021) used a mobile writing app with students with dysgraphia. The results indicated that the use of a mobile app increased the students’ on-task duration and helped with their writing skills.…”
Section: Mobile Learning and Purposementioning
confidence: 99%
“…They found that mobile apps might be a reliable option for students with disabilities who cannot afford assistive technologies. Hopcan and Tokel (2021) used a mobile writing app with students with dysgraphia. The results indicated that the use of a mobile app increased the students’ on-task duration and helped with their writing skills.…”
Section: Mobile Learning and Purposementioning
confidence: 99%
“…In this context, many systems and mobile applications have been developed to perceive and comprehend their visual surroundings using handwritten text recognition techniques [2][3][4][5]. The goal of these systems is to read street signs and allow easier automated navigation [6,7], search and index a large number of images or videos on the Internet [8][9][10], detect product labels for autonomous stores [11] or help in real-time text recognition of translations on smartphones [12].…”
Section: Introductionmentioning
confidence: 99%
“…The main purpose of this study is to reveal the views of special education teachers on a mobile writing application after its use. Previous studies have developed a mobile writing application (Hopcan et al, 2019) and examined its effectiveness (Hopcan & Tokel, 2021). In this current study, a qualitative method was used to reveal the views of special education teachers on the mobile writing application after its use.…”
mentioning
confidence: 99%
“…It is recommended to be used in the education of students with writing disabilities. In another study, a mobile writing application was developed (Hopcan et al, 2019) and its effectiveness was examined (Hopcan & Tokel, 2021). There was an improvement in students' writing skills after using this application (Hopcan & Tokel, 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation